Potential of White Oyster Mushroom to Improve Male Fertility : A Systematic Review - Tri Andrianto, Yoga Fathur; Ardinata, Dedi; Ichwan, Muhammad (International Journal of Ecophysiology, 2024)
ABSTRACT : Infertility in men is a health problem that is quite often experienced these days. One of the causes of idiopathic infertility in men is oxidative stress (SO). Several previous research results have previously been presented which prove that poor sperm quality is associated with an increase in reactive oxygen species (ROS) due to SO. White Oyster Mushroom (Pleurotus ostreatus) is a mushroom that is rich in antioxidants which has great potential to reduce the occurrence of reactive oxygen species (ROS) which reach high levels of SO so it is thought to be useful in improving sperm quality. Keyword : Infertility, Sperm, Pleurotus ostreatus. ABSTRAK : Infertilitas pada pria merupakan masalah kesehatan yang cukup sering dialami saat ini. Salah satu penyebab infertilitas idiopatik pada pria adalah stres oksidatif (SO). Beberapa hasil penelitian terdahulu telah dipaparkan sebelumnya yang membuktikan bahwa kualitas sperma yang buruk berhubungan dengan peningkatan spesies oksigen reaktif (ROS) akibat SO. Jamur Tiram Putih (Pleurotus ostreatus) merupakan jamur yang kaya akan antioksidan yang berpotensi besar dalam menurunkan terjadinya spesies oksigen reaktif (ROS) yang mencapai kadar SO tinggi sehingga diduga bermanfaat dalam meningkatkan kualitas sperma.